AIR QUALITY MONITORING OF KALABAHI-ALORâ€™S SEAPORT-EAST OF NUSA TENGGARA - Rikson Siburian; Minsyahril Bukit; Herlince Sihotang; Saur Lumban Raja; Minto Supeno; Cristina Simanjuntak; Nurhaida Pasaribu; Sri Pratiwi Aritonang (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Evaluation of environment of seaport is needed as well as our responsibility to nature sustainability. The Alorâ€™s seaport belongs to Pelindo III. In order to know the air quality of Alorâ€™s seaport, we did this study. Our aims are to know level quality of air at Alorâ€™s seaport and compare to the government regulation. This study refers to Pararosaniline (SOx), Saltzman (NOx), Particle Calculation (dust) and decibel (noisy) methods. We used four locations, those are A-1 (Entrance gate of PELINDO (8013â€™09.12â€S, 124031â€™07.21â€E)); A-2 (In front of passengers terminal (8013â€™08.75â€S, 124031â€™01.60â€E)); A-3 (Exit gate Kalabahiâ€™s seaport (8013â€™08.2â€S, 124031â€™00.87â€E)) and A-4 (In front of port of the people (8011â€™09.12â€S, 124031â€™07.21â€E)). Results show that the averages level of SOx, NOx and dust of A-1, A-2 and A-3 are 103.01, 104.65 and 107.47 (Âµg/Nm3), 37.87, 30.62, and 39.73 (Âµg/Nm3), 56.64, 47.47 and 50.72 (Âµg/Nm), respectively. On the other hand, the level of noisy of A-1, A-2, A-3 and A-4 are 68.76, 65.69, 65.20 and 73.60 (dBA), respectively. Base on all of data, we conclude that the air quality of Alorâ€™s seaport is still appropriate according to government regulation (PP. No. 4, 1999).